The HIV-1 late domain-2 S40A polymorphism in antiretroviral (or ART)-exposed individuals influences protease inhibitor susceptibility. Issue 1 (December 2016) - Watanabe, Susan; Simon, Viviana; Durham, Natasha; Kemp, Brittney; Machihara, Satoshi; Kemal, Kimdar; Shi, Binshan; Foley, Brian; Li, Hongru; Chen, Benjamin; Weiser, Barbara; Burger, Harold; et al.
Abstract Background The p6 region of the HIV-1 structural precursor polyprotein, Gag, contains two motifs, P7 TAP11 and L35 YPLXSL41, designated as late (L) domain-1 and -2, respectively . These motifs bind the ESCRT-I factor Tsg101 and the ESCRT adaptor Alix, respectively, and are critical for efficient budding of virus particles from the plasma membrane. L domain-2 is thought to be functionally redundant to PTAP. To identify possible other functions of L domain-2, we examined this motif in dominant viruses that emerged in a group of 14 women who had detectable levels of HIV-1 in both plasma and genital tract despite a history of current or previous antiretroviral therapy. Results Remarkably, variants possessing mutations or rare polymorphisms in the highly conserved L domain-2 were identified in seven of these women. A mutation in a conserved residue (S40A) that does not reduce Gag interaction with Alix and therefore did not reduce budding efficiency was further investigated. This mutation causes a simultaneous change in the Pol reading frame but exhibits little deficiency in Gag processing and virion maturation. Whether introduced into the HIV-1 NL4-3 strain genome or a model protease (PR) precursor, S40A reduced production of mature PR. This same mutation also led to high level detection of two extended forms of PR that were fairly stable compared to the WT in the presence of IDV at various concentrations; one of the extended forms was effective intrans processing even at micromolar IDV. Conclusions Our results indicate that L domain-2, considered redundant in vitro, can undergo mutations in vivo that significantly alter PR function. These may contribute fitness benefits in both the absence and presence of PR inhibitor.